A View on Genomic Medicine Activities in Africa: Implications for Policy - Jongeneel, C. Victor; Kotze, Maritha J.; Bhaw-Luximon, Archana; Fadlelmola, Faisal M.; Fakim, Yasmina J.; Hamdi, Yosr; Kassim, Samar Kamal; Kumuthini, Judit; Nembaware, Victoria; Radouani, Fouzia; Tiffin, Nicki; Mulder, Nicola (Frontiers in Genetics, 2022)
Genomics policy development involves assessing a wide range of issues extending from specimen collection and data sharing to whether and how to utilize advanced technologies in clinical practice and public health initiatives. A survey was conducted among African scientists and stakeholders with an interest in genomic medicine, seeking to evaluate: ● Their knowledge and understanding of the field ● The institutional environment and infrastructure available to them ● The state and awareness of the field in their country ● Their perception of potential barriers to implementation of precision medicine We discuss how the information gathered in the survey could instruct the policies of African institutions seeking to implement precision, and more specifically, genomic medicine approaches in their health care systems in the following areas: ● Prioritization of infrastructures ● Need for translational research ● Information dissemination to potential users ● Training programs for specialized personnel ● Engaging political stakeholders and the public